2021
DOI: 10.3390/cells10112959
|View full text |Cite
|
Sign up to set email alerts
|

The Gut–Liver Axis in Chronic Liver Disease: A Macrophage Perspective

Abstract: Chronic liver disease (CLD) is a growing health concern which accounts for two million deaths per year. Obesity, alcohol overconsumption, and progressive cholestasis are commonly characterized by persistent low-grade inflammation and advancing fibrosis, which form the basis for development of end-stage liver disease complications, including hepatocellular carcinoma. CLD pathophysiology extends to the intestinal tract and is characterized by intestinal dysbiosis, bile acid dysregulation, and gut barrier disrupt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 378 publications
(543 reference statements)
0
30
0
5
Order By: Relevance
“…Already 2012 Boonstra et al demonstrated the role of colonic involvement as distinct phenotypical risk factor for PSC also in CD ( 28 ). A causal relationship may exist for translocation of bacterial components through an inflamed and leaky colon into the portal circulation and associated liver inflammation through macrophages and gut-derived T cells ( 29 ). Interestingly, we have not recorded any PSC in L2 CD in our pediatric registry.…”
Section: Discussionmentioning
confidence: 99%
“…Already 2012 Boonstra et al demonstrated the role of colonic involvement as distinct phenotypical risk factor for PSC also in CD ( 28 ). A causal relationship may exist for translocation of bacterial components through an inflamed and leaky colon into the portal circulation and associated liver inflammation through macrophages and gut-derived T cells ( 29 ). Interestingly, we have not recorded any PSC in L2 CD in our pediatric registry.…”
Section: Discussionmentioning
confidence: 99%
“…К тому же равновесие провоспалительных и противовоспалительных цитокинов может сдвигать течение основного заболевания в сторону прогрессирования или регенерации у пациентов с хроническими прогрессирующими заболеваниями печени [12,33,34,55,[56][57][58][59].…”
Section: бактериальные патоген-ассоциированные паттерны и иммунный ответunclassified
“…Концепция ПИО подразумевает и обратный путь -путь воздействия на микробиом, колонизирующий кишечник. Данная регуляция в полной мере отражает двунаправленность концепции ПИО [12,55,57,62]. Таким образом, печень «очерчивает» микробиоту кишечника посредством высвобождения IgA и желчи.…”
Section: печеночная регуляция микробиоты кишечникаunclassified
See 2 more Smart Citations